Infectious crystalline keratopathy predominantly affecting the posterior cornea - Mesiwala, Nisreen K (e-Century Publishing Corporation, 2014)
A case of infectious crystalline keratopathy that affects mainly the posterior stroma is presented. Crystalline infiltrates presented after multiple epithelial defects and chronic topical steroid use following a penetrating keratoplasty in this patient. His epithelial defects persisted and given the deep location of the crystalline infiltrates, a penetrating keratoplasty was performed again. Slit-lamp photo demonstrates the crystalline plaque. Confocal microscopy also documents the aggregates of crystal-like structures. Histology slides are also presented that show the disruption of the stromal-Descemet interface and the predominance of pathology confined to the posterior stroma which has been documented in the literature as a rare finding.